PENGARUH KEGIATAN MUSYAWARAH GURU MATA PELAJARAN IPS TERHADAP KOMPETENSI PROFESIONAL SMP DI KABUPATEN MEMPAWAH - Yani, Sri; Aminuyati, Aminuyati; Genjik S, Bambang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to determine the effect of the integrated social studies teacher (ISST) social studies activities on the professional competence of junior high school integrated social science teachers in Mempawah Regency. This study uses a quantitative method with two variables, they are Integrated Subject Teacher (ISST) social studies (X) and professional competence (Y). Determination of the sample used is the Slovin formula. The data source of this research is Integrated Social Sciences teachers who teach in Mempawah District with a sample of 55 people. Data collection techniques used consisted of: 1. questionnaire, 2. interview, and 3. documentation. Data obtained from the results of respondents' questionnaires and from the results of interviews with MGMP administrators and interviews with Integrated Social Studies subject supervisors from the District Education Office in Mempawah. Then do the validity and reliability test, the analysis prerequisite test using the normality test and linearity test. Next test the hypothesis using simple regression analysis. From the regression results obtained by the equation Y = 30,803 + 1,186 x. Test the significance of the regression equation with the t test obtained t arithmetic = 11.92 and t table 2.006 which means significant (t arithmetic> t table), then obtained significance value 0,000 <0.05 which means there is a positive and significant effect. Obtained results there is a relationship between ISST activities (variable X) with a level of professional competence (variable Y) of 0.851 and the magnitude of the contribution of the influence of ISST R2 (square) activities of 0.725 or 72.5% on professional competence. So there is an influence between ISST activities with the professional competence of Junior High School Integrated Social Sciences teachers in Mempawah Regency.Â Keywords: Influence, ISST activities, Professional Competence